2020
DOI: 10.5114/amsad.2020.95877
|View full text |Cite
|
Sign up to set email alerts
|

State and trait anxiety in islander cardiac patients: associated factors and the impact of perceived social support

Abstract: Introduction: Cardiac patients frequently experience elevated levels of anxiety, which may influence clinical outcomes. Perceived social support is a precious resource with which to minimise anxiety. The aim of the study was to explore levels of perceived social support, levels of anxiety (state and trait), and the associated factors as well as the impact of patents' characteristics and social support on anxiety. Material and methods: The study sample consisted of 82 island inhabitant patients with cardiac pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“… 21 Also, an increase in social support either by significant ones, family, or friends leads to a decrease in state and trait anxiety. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Also, an increase in social support either by significant ones, family, or friends leads to a decrease in state and trait anxiety. 24 …”
Section: Discussionmentioning
confidence: 99%
“…This finding emphasizes the need to evaluate patients’ perspectives that exert a significant influence on cardiac disease, such as changing health behaviors, following recommended treatments, and rehabilitation. 24 More dependency-related issues are anticipated to emerge at the forefront of clinical practice along with PM technology progression. Technological advances in electronic device implantation are inevitably associated with several improvements in health and longevity but simultaneously induce a degree of care of advanced complexity.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Moreover, an increase in fatigue indicates an increase in deterioration of the quality of life 11 Clinical outcomes in HF depend also on psychological stress in the form of anxiety and depression, 12 while the more the support, the less the anxiety. 13 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study on a group of Taiwanese youth found that having an inadequate amount of support from one's kin was directly related to heightened insomnia complaints ("β = −0.06") (p. 1) [47], while another study on a group of American teenagers has demonstrated that such an experience could also be indirectly predictive of greater insomnia complaints (in this case, at the conclusion of their initial high school year by means of its effect on such sleep difficulties at the start of it) (B = "−.01") (p. 1033) [48]. This is in juxtaposition to a handful of other findings that have either contradicted these outcomes (e.g., [52]) or has suggested that the insomnia-mitigating benefit of help and comfort provided by others may not be exclusive to the support one can obtained from kin (e.g., [53]). Although there were emerging evidence demonstrating the existence of the kin support-insomnia symptoms relationship across a longer timeframe (e.g., [48]), most of the empirical investigations on this association were likewise carried out at a single timepoint.…”
Section: Reduced Support From One's Kinmentioning
confidence: 75%